Tremors - 1958-; 1947-; Gross, Michael; 1942-; Ward, Fred; Bacon, Kevin; Maddock, Brent; Wilson, S. S.; 1950- (Universal City, CA, 1998)
Two country handymen and a seismology student discover a desolate town infested with gigantic man-eating creatures that live underground.
Keywords: Nevada; Tourism; Drama; Nevada; Monsters; Drama; Nevada; Drama; Fiction films; Feature films; Horror films; Largometrajes; Pel?culas de horror; Horror films; Grabaciones de v?deo para los de audici?n disminuido; Video recordings for the hearing impaired; Video recordings for the hearing impaired; Feature films; Drama; Fiction films; Horror films